Preparation of Lignite Dust Suppressant by Compound Surfactants and Effect of Inorganic Salt on Dust Suppressant - Jian He; Hao Shu; Lei Zhang; Lei Zhang; Yang Jia; Lu Zhao; Xin Wen (Advances in Materials Science and Engineering)
In order to improve the safety, operability, and cleanability of the dust suppressant, this paper uses the surfactant monomers selected in the previous experiment as the main material formula and adds the inorganic salt as the synergist to prepare the dust suppressant for the PMX. The wetting property of the solution was characterized by the surface tension and contact angle of the pressed coal pieces. The sedimentation experiment was used to screen the compounding system of the surfactant. Finally, the dust suppressant was used to reduce the dust of the PMX in the coal dust simulation system. The results show that (1) the surfactant compounding system can effectively improve the wetting property and the sedimentation time of coal dust. The fast penetration T (0.06%), SDBS (0.15%), and APG (0.20%) are the preferred main ingredients. (2) Adding inorganic salts on the basis of compounding, according to the effect of inorganic salts on the effect of dust suppressant, it is concluded that NaCl (1.00%) is the best synergist. (3) In order to save costs, reduce the amount of surfactant. According to the simulated dust reduction experiment, formula N: anionic surfactant SDBS (0.06%), anionic surfactant fast-permeability T (0.06%), and inorganic salt NaCl (1.00%) are the best for PMX dust fall.